2014 YEAR OF THE HORSE THE WORLD ECONOMY - Herrera García, Beatriz (2014)
The world economy will improve this year, while maintaining vulnerability risks.Specifically, it is estimated according to the LINK Project and Model DESA, an increase of three percent (3.0%) on a global scale, higher rate reached 2.1% in 2013.In 2014, it is expected that developing countries con-tinue to be the drivers of global economic growth and is contemplated; also that the policies adopted in the United States and Japan contribute to these economies to rebound and also promote further economic growth in the world. Also in the euro area (EU), according to recent forecasts, an increase in credit, less restrictive fiscal policies and a rebound in exports contribute to achieving positive growth rates. However, it is expec-ted that growth in the euro area will remain at a low level for a long time. But a strong recovery of the US economy and China’s return to sustainable growth facilitate recovery in the EU.